The diary of William Mackenzie, the first international railway contractor - Mackenzie, William, 1794-1851 (Thomas Telford, 2000)
The diary that Mackenzie kept during the height of his career has been transcribed, documenting his daily life and detailing his business travels. It presents a record of his life and work affording insights for economic, social and engineering historians.